Corrigendum to “Quality-assurance of heat-flow data: the new structure and evaluation scheme of the IHFC Global Heat Flow Database” [Tectonophysics 863 (2023) / 229976] - Sven Fuchs; Ben Norden; Florian Neumann; Norbert Kaul; Akiko Tanaka; Ilmo T. Kukkonen; Christophe Pascal; Rodolfo Christiansen; Gianluca Gola; Jan Šafanda; Orlando Miguel Espinoza-Ojeda; Ignacio Marzan; et al. (Tectonophysics, 2026)

Agronomic performance of six carrot genotypes grown under organic farming conditions - Marlene Sandra Fuchs; Jens Hartung; Simone Graeff-Hönninger (Organic Agriculture, 2025)
Carrots play a crucial role in organic farming, where selecting the suitable genotype is essential due to the limited use of pesticides and fertilizers. Due to the variability in hybrid offspring, open-pollinated genotypes are becoming increasingly attractive. This study evaluated one hybrid (H), two open-pollinated genotypes (OP1 and OP2), and three new breeding lines (BL1, BL2, and BL3) under organic conditions. Six field trials were conducted in Germany over two years (2020/2021) to assess marketable and non-marketable yield, dry matter (DM) content, morphological traits, disease resistance against Alternaria dauci and Erysiphe heraclei and leaf stability determined by applying pulling force on foliage and rating on a 1 (very unstable) to 9 (very stable) scale. From mixed-model analysis, significant differences were observed in four traits across genotypes. BL1 had the lowest yield (49.39 t ha −1 ), while OP2 had the highest (72.38 t ha −1 ). BL1 showed the highest DM content (15.0%), while OP2 had the highest DM yield (9.4 t ha −1 ). Leaf stability varied, with OP2 showing high stability (7.88) compared to H (5.64). The results highlight OP2 as suitable for organic farming due to its high yield and leaf stability. Open-pollinated genotypes, including new breeding lines, offer competitive options to hybrids, providing farmers with a broader range of choices. Further research should focus on testing additional genotypes under diverse conditions to support organic carrot production.

The Local Turn in a Global Sea: Identifying Sustainability Trade‐Offs in Regionalized Marine Aquaculture Systems - Gesche Krause; Ramón Filgueira; Nesar Ahmed; Karen A. Alexander; Furqan Asif; Lucia Fanning; Sebastian C. A. Ferse; Nike Fuchs; Jon Grant; Jordi Guillen; Christina Hörterer; Teresa R. Johnson; et al. (Reviews in Aquaculture, 2025)
Marine aquaculture, like the broader seafood industry, relies heavily on international trade and global supply chains for both production and sales. Recent global disruptions, including the COVID‐19 pandemic, the Russian invasion of Ukraine, the conflicts in the Middle East, and trade tensions, have exposed the social and economic vulnerabilities inherent in a globalized production system. In response, these events have sparked growing interest in transitioning to localized and regional supply chain models. Calls to “buy national” and support domestic economies highlight this trend toward regionalization. This study explores the sustainability implications of regionalizing marine aquaculture by examining the four key segments of the supply chain. These are (1) upstream inputs and resources (2) aquaculture production (3) downstream added value‐processing and (4) distribution–transportation. Potential benefits of regional production models include increased resilience to disruptions, lower transportation‐related carbon emissions, and support for local economies. However, such models may also introduce trade‐offs, including reduced production efficiency, supply and sales limitations, and implications for social, cultural, and governance structures. Our analysis reveals that the sustainability outcomes of regionalization are complex and context‐dependent. It is influenced by the specific characteristics of existing supply chains and the regional contexts in which they operate. While regionalization may offer advantages in certain contexts, it does not guarantee improved sustainability. Thus, it is crucial to critically assess the assumption that regionalization inherently leads to improved sustainability outcomes. Proactive evaluation of these dynamics is essential to develop strategies that maximize benefits while addressing potential trade‐offs.

(Bio)degradation of biopolymer and biocomposite in deep-sea environments - Alexandre Chamley; Christophe Baley; Nicolas Gayet; Jozée Sarrazin; Sandra Fuchs; Floriane Freyermouth; Peter Davies (Marine Pollution Bulletin, 2024)

What roles can democracy labs play in co-creating democratic innovations for sustainability? - Inês Campos; Doris Fuchs; Petteri Repo; Wander Jager; Christian Klöckner; Shaoni Wang; David Lamas; Francesc Cots; Eugenio Barchiesi; Erica Löfström; Daniel Peniche; Yulia Sion; et al. (Socio-Ecological Practice Research, 2024)
This perspective essay proposes Democracy Labs as new processes for developing democratic innovations that help tackle complex socio-ecological challenges within an increasingly unequal and polarised society, against the backdrop of democratic backsliding. Next to the current socio-ecological crisis, rapid technological innovations present both opportunities and challenges for democracy and call for democratic innovations. These innovations (e.g., mini-publics, collaborative governance and e-participation) offer alternative mechanisms for democratic participation and new forms of active citizenship, as well as new feedback mechanisms between citizens and traditional institutions of representative democracy. This essay thus introduces Democracy Labs, as citizen-centred processes for co-creating democratic innovations to inspire future transdisciplinary research and practice for a more inclusive and sustainable democracy. The approach is illustrated with examples from a Democracy Lab in Lisbon, reflecting on requirements for recruiting participants, the relevance of combining sensitising, reflection and ideation stages, and the importance of careful communication and facilitation processes guiding participants through co-creation activities.

The fungal predominance in stem collar necroses of Fraxinus excelsior: a study on Hymenoscyphus fraxineus multilocus genotypes - Sandra Peters; Nina Gruschwitz; Steffen Bien; Sebastian Fuchs; Ben Bubner; Viktoria Blunk; Gitta Jutta Langer; Ewald Johannes Langer (Journal of Plant Diseases and Protection, 2024)
Over the past decades, European ash trees in Germany have been affected by ash dieback, reducing their vigour and mechanical resistance. Those trees that also have stem collar necroses and the resulting stem rot are particularly affected. In this study, multilocus genotypes (MLGs) of Hymenoscyphus fraxineus and their interactions with other fungi from stem collar necroses were analysed. Ten ash trees from three different adjacent forest stands in central Germany were sampled. A total number of 716 isolates were obtained from stem collar necroses from these ten trees. Microsatellite analysis was successfully performed on 274 isolates identified as H. fraxineus and 26 MLGs were revealed. The number of MLGs varied from one to seven per tree and did not correspond to the number or severity of necroses. A striking result was that five of the MLGs occurred in two trees. All other MLGs occurred independently in only one tree, as expected. Our data show that when multiple MLGs were observed in a tree, one of the MLGs outnumbered the others, indicating that H. fraxineus is a primary coloniser of stem collar necroses. A total of 61 morphotypes, including H. fraxineus , were identified and discussed, comprising endophytic, saprotrophic and pathogenic fungi. Between five and 19 different fungi were found per stem collar necrosis. The majority of all isolated morphotypes were Ascomycota (82%), with the most common orders being Xylariales and Hypocreales . The most frequently isolated morphotypes, apart from H. fraxineus , were Armillaria sp. and Diplodia fraxini . Together they account for more than three quarters of all assigned isolations. Apart from H. fraxineus , only Diplodia fraxini was isolated from all ten trees.

Ash dieback assessments on intensive monitoring plots in Germany: influence of stand, site and time on disease progression - Sebastian Fuchs; Henriette Häuser; Sandra Peters; Luisa Knauf; Felix Rentschler; Georgia Kahlenberg; Ralf Kätzel; Jan Evers; Uwe Paar; Gitta Jutta Langer (Journal of Plant Diseases and Protection, 2024)
Since 2002, ash dieback caused by the invasive fungus Hymenoscyphus fraxineus has been observed in Germany. The pathogen and its associated symptoms have fatal consequences for the vitality and survival of European ash ( Fraxinus excelsior L.), an economically and ecologically important tree species. This study analyses the ash monitoring results of eleven intensive monitoring plots of the FraxForFuture research network distributed across Germany and focuses on within-stand differences of symptoms in dependence of small-scale site and tree properties. A cohort of 1365 ash trees was surveyed six times over three years, testing and applying a summer and a winter version of a nationally standardised ash dieback assessment key. The main disease symptoms (crown dieback and basal lesions) were more pronounced in areas with higher ash density, in edaphically moist areas (hydromorphic soils), on younger/smaller ash trees, and generally increased over time. However, the trend over time differed between single plots. In case of considering only the surviving part of the ash populations, crown condition even improved in 6/11 plots, indicating a selection process. Large basal lesions at the beginning of the observation period were a very good predictor for deadfall probability, especially on trees with lower stem diameter. Generally, ash dieback related symptoms at stem and crown were highly correlated. Silvicultural management practice in the past that actively pushed ash towards the moister end of its water demand spectrum has to be questioned in the light of ash dieback. Cost-intensive ash re-cultivation in the future—possibly with less dieback-susceptible progenies—should avoid pure ash stands and hydromorphic soil conditions.

Multi-sensor characterization for an improved identification of polymers in WEEE recycling - Andréa de Lima Ribeiro; Margret C. Fuchs; Sandra Lorenz; Christian Röder; Johannes Heitmann; Richard Gloaguen (Waste Management, 2024)

High connectivity among Vesicomyid bivalves from cold seeps and deep-sea fans of Congo - Mohamad Hassan; Sara Teixeira; Carole Decker; Sandra Fuchs; Olivier Mouchel; Karine Olu; Sophie Arnaud-Haond (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Quality-assurance of heat-flow data: The new structure and evaluation scheme of the IHFC Global Heat Flow Database - Sven Fuchs; Ben Norden; Florian Neumann; Norbert Kaul; Akiko Tanaka; Ilmo T. Kukkonen; Christophe Pascal; Rodolfo Christiansen; Gianluca Gola; Jan Šafanda; Orlando Miguel Espinoza-Ojeda; Ignacio Marzan; et al. (Tectonophysics, 2023)

Fungi associated with stem collar necroses of Fraxinus excelsior affected by ash dieback - Sandra Peters; Sebastian Fuchs; Steffen Bien; Johanna Bußkamp; Gitta Jutta Langer; Ewald Johannes Langer (Mycological Progress, 2023)
In recent decades the vitality and physical stability of European ash trees in Germany have been reduced by European ash dieback, especially when associated with stem collar necroses and rots. This study was carried out to investigate the composition of the fungal communities associated with stem collar necroses. Filamentous fungi were isolated from 58 ash trees out of nine forest stands in northern, eastern, and central Germany. Obtained isolates were identified to a genus or species level by means of morphological and molecular analyses. In total 162 morphotypes including endophytic, saprotrophic, and pathogenic fungi were isolated. For 33 species found no prior reports from Fraxinus excelsior were recognised, including Cryptostroma corticale and Diplodia sapinea . None of the identified species were found at all studied sites, though Diplodia fraxini was the most common fungus with regard to frequency within all isolates , occurring at seven sample sites. This species is followed by Hymenoscyphus fraxineus , Armillaria spp., Neonectria punicea , Diaporthe cf. eres , Fusarium cf. lateritium , and Paracucurbitaria sp. in order of frequency within all isolates. The aforementioned species are characterised and analysed in respect to their occurrence in stem collar necroses and at sample sites. The influence of site conditions on the fungal composition was described for five intensively sampled sites with a minimum of five studied trees (Schwansee, Rhüden, Berggießhübel, Satrup, and Schlangen). The sampling site of Schlangen was further subdivided into four subplots with different positions in the terrain. In the remaining four extensive sample sites, either one or two trees, respectively, were sampled and analysed (Oranienbaumer Heide, Woltershausen, Wolfenbüttel, and Neuhege). Over all sample sites, fungal communities of symptomatic stem tissue are similar concerning the most frequent fungi, but vary greatly according to singularly isolated fungi.

Chiral-based mechanical metamaterial with tunable normal-strain shear coupling effect - Mathias Fleisch; Andreas Thalhamer; Gerald Meier; Philipp Arno Franz Huber; Peter Filipp Fuchs; Gerald Pinter; Sandra Schlögl; Michael Berer (Engineering Structures, 2023)

FraxForFuture—research on European ash dieback in Germany - Gitta Jutta Langer; Sebastian Fuchs; Johannes Osewold; Sandra Peters; Falk Schrewe; Maia Ridley; Ralf Kätzel; Ben Bubner; Jörg Grüner (Journal of Plant Diseases and Protection, 2022)
European ash dieback caused by the alien, invasive ascomycete species Hymenoscyphus fraxineus currently represents, along with its side effects, the greatest threat to common ash ( Fraxinus excelsior ) trees in Europe. The disease is widely distributed in Germany and present in all regions where common ash is growing. In order to study European ash dieback in Germany and to develop management strategies to conserve common ash as a forest tree species, the concerted, interdisciplinary research project FraxForFuture was initiated. FraxForFuture consist of an association of five sub-networks: FraxConnect, FraxMon, FraxGen, FraxPath, and FraxSilva. In total, 27 individual projects conduct research on the epidemiology of the disease, the pathogen and the preservation of ash, including various control, breeding, and silvicultural strategies. The main goals of the FraxForFuture network and the sub-networks as well as essential information about the network of common research plots are provided.

Hybrid conferences: opportunities, challenges and ways forward - Eleonora Puccinelli; Daniela Zeppilli; Paris V. Stefanoudis; Annaïg Wittische-Helou; Marjorie Kermorgant; Sandra Fuchs; Lénaïck Menot; Erin E. Easton; Alexandra A-T. Weber (Frontiers in Marine Science, 2022)
Hybrid conferences are in-person events that have an online component. This type of meeting format was rare before the COVID-19 pandemic, but started to become more common recently given the asynchronous global progression of the pandemic, the uneven access to vaccines and different travel regulations among countries that led to a large proportion of participants being unable to attend conferences in person. Here we report the organization of a middle-sized (581 participants: 159 onsite, 422 online) international hybrid conference that took place in France in September 2021. We highlight particular organizational challenges inherent to this relatively new type of meeting format. Furthermore, we surveyed both in-person and online participants to better understand their conference experience and to propose improvements based on the feedback received. Finally, we compare the advantages and disadvantages of three types of conferences (onsite-only, online-only and hybrid) and suggest that hybrid events should be favored in the future because they offer the most flexibility to participants. We conclude by proposing suggestions and ways forward to maximize accessibility and inclusivity of hybrid conferences. Our study brings novel insights on the challenges and opportunities created by hybrid conferences, by reporting not only the organizing committee experience but also by considering the participants’ perspective.

Designing real-world laboratories for sustainable urban transformation: addressing ambiguous roles and expectations in transdisciplinary teams - Sandra Huning; C. Räuchle; M. Fuchs (Sustainability Science, 2021)
This paper reflects upon the potential of real-world laboratories (RWLs) to promote sustainable urban development. RWLs strive for knowledge production through collective action in experimental settings. Their implementation in urban studies faces two major challenges: (1) the ambiguity of roles university researchers need to fill, and (2) the variety of expectations among team members from different institutional backgrounds. Based on research in one trans-European and three German RWLs, we propose a stronger focus on team development to help researchers in RWLs address these challenges more systematically. In particular, this means support in terms of resources and infrastructure (time, space, and training). We argue that the improvement of RWL team performance has great impact on the potentials of RWLs in transformative urban studies. Thus, the article contributes to the ongoing debate on the city as a laboratory and site of experimentation in times of multiple crises.

Journal Club - Volkmar Braun; Georg Fuchs; Michael Schloter; Torsten Schubert; Jochen Graw; Daniela Kruck; Johannes Sander; Gerhart Drews; Stefan Schild; Klaus Hantke; Sandra Wiegand; Alexander Westermann; et al. (BIOspektrum, 2020)

Characteristics of meiofauna in extreme marine ecosystems: a review - Daniela Zeppilli; Daniel Leduc; Christophe Fontanier; Diego Fontaneto; Sandra Fuchs; Andrew J. Gooday; Aurélie Goineau; Jeroen Ingels; Viatcheslav N. Ivanenko; Reinhardt Møbjerg Kristensen; Ricardo Cardoso Neves; Nuria Sanchez; et al. (Marine Biodiversity, 2018)

Rapid colonisation by nematodes on organic and inorganic substrata deployed at the deep-sea Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) - Daniela Zeppilli; Ann Vanreusel; Florence Pradillon; Sandra Fuchs; Perrine Mandon; Tristan James; Jozée Sarrazin (Marine Biodiversity, 2015)

High connectivity across the fragmented chemosynthetic ecosystems of the deep A tlantic E quatorial B elt: efficient dispersal mechanisms or questionable endemism? - Sara Teixeira; Karine Olu; Carole Decker; Regina L. Cunha; Sandra Fuchs; Stéphane Hourdez; Ester A. Serrão; Sophie Arnaud‐Haond (Molecular Ecology, 2013)
Chemosynthetic ecosystems are distributed worldwide in fragmented habitats harbouring seemingly highly specialized communities. Yet, shared taxa have been reported from highly distant chemosynthetic communities. These habitats are distributed in distinct biogeographical regions, one of these being the so‐called A tlantic E quatorial B elt ( AEB ). Here, we combined genetic data ( COI ) from several taxa to assess the possible existence of cryptic or synonymous species and to detect the possible occurrence of contemporary gene flow among populations of chemosynthetic species located on both sides of the A tlantic. Several E volutionary S ignificant U nits ( ESUs ) of Alvinocarididae shrimp and V esicomyidae bivalves were found to be shared across seeps of the AEB . Some were also common to hydrothermal vent communities of the M id‐ A tlantic R idge ( MAR ), encompassing taxa morphologically described as distinct species or even genera. The hypothesis of current or very recent large‐scale gene flow among seeps and vents was supported by microsatellite analysis of the shrimp species A lvinocaris muricola / A lvinocaris markensis across the AEB and MAR . Two nonmutually exclusive hypotheses may explain these findings. The dispersion of larvae or adults following strong deep‐sea currents, possibly combined with biochemical cues influencing the duration of larval development and timing of metamorphosis, may result in large‐scale effective migration among distant spots scattered on the oceanic seafloor. Alternatively, these results may arise from the prevailing lack of knowledge on the ocean seabed, apart from emblematic ecosystems (chemosynthetic ecosystems, coral reefs or seamounts), where the widespread classification of endemism associated with many chemosynthetic taxa might hide wider distributions in overlooked parts of the deep sea.

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Microphthalmia, parkinsonism, and enhanced nociception in Pitx3 416insG mice - Michael Rosemann; Alesia Ivashkevich; Jack Favor; Claudia Dalke; Sabine M. Hölter; Lore Becker; Ildikó Rácz; Ines Bolle; Martina Klempt; Birgit Rathkolb; Svetoslav Kalaydjiev; Thure Adler; et al. (Mammalian Genome, 2010)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)